The Impact of COVID-19 Pandemic on Individuals With Pre-existing Obsessive-Compulsive Disorder in the State of Qatar: An Exploratory Cross-Sectional Study - Siddiqui, Maryam; Wadoo, Ovais; Currie, James; Alabdulla, Majid; Al Siaghy, Areej; AlSiddiqi, Abdulkarim; Khalaf, Eslam; Chandra, Prem; Reagu, Shuja (Frontiers in Psychiatry, 2022)
Background: Published evidence about impact of the Coronavirus disease 2019 (COVID-19) pandemic on Obsessive-Compulsive Disorder (OCD) is conflicting. Most studies suggest an increase in severity of OCD in people with pre-existing OCD, whereas some do not. Aim: Given the conflicting evidence globally and lack of data from the Arab world, we aimed to explore the impact of pandemic on obsessive compulsive symptoms in adults with pre-existing OCD. Methods: A telephonic questionnaire-based cross-sectional study among adults with pre-existing OCD and specifically with fear of contamination and washing compulsions being major symptom dimension of OCD. The severity of OCD during pandemic was compared with their pre-pandemic scores. The severity of OCD was assessed using the Yale-Brown Obsessive-Compulsive Scale (YBOCS). Results: Those with the duration of diagnosis of OCD of less than 10 years, showed a statistically significant increase in the mean Yale-Brown Obsessive-Compulsive Scale score of 5.54 from pre pandemic to during pandemic, which was significant at p = 0.006. This significance was maintained across the Compulsive and Obsessive subsets of the scale. Conclusion: Adults with pre-existing OCD with fear of contamination reported a statistically significant increase in severity of obsessive-compulsive symptoms only if the duration of their OCD diagnosis was relatively shorter (less than 10 years). In context of the conflicting evidence regarding worsening of OCD symptoms due to the unique infection control measures of this pandemic, this study highlights the importance of the impact of the duration of the disorder and the subtype of the disorder. Such classification might help public health resources to be directed better at those most at risk and also help us understand the very nature of this disorder better.